Procollagen-lysine 2-oxoglutarate 5-dioxygenases are responsible for 5R-hydroxylysine modification of therapeutic T-cell bispecific monoclonal antibodies produced by Chinese hamster ovary cells - Bauer, Niels; Boettger, Marco; Papadaki, Styliani; Leitner, Tanja; Klostermann, Stefan; Kettenberger, Hubert; Georges, Guy; Larraillet, Vincent; Gluhacevic von Kruechten, Dino; Hillringhaus, Lars; Vogt, Annette; Ausländer, Simon; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
We present a detailed mass spectrometric analysis of three 2 + 1 T-cell bispecific monoclonal antibodies (TCB mAbs), where an unexpected +15.9950 Da mass shift in tryptic peptides was observed. This modification was attributed to the occurrence of 5R-hydroxylysine (Hyl) using a hybrid LC–MS/MS molecular characterization and CRISPR/Cas9 gene deletion approach. The modification was found at various sites within TCB mAbs, with a conspicuous hot spot motif mirroring a prior observation where Hyl was mapped to the CH1–VH Fab domain interface of IgGs. In contrast to the preceding report, our structural modeling analysis on TCB mAbs unveiled substantial differences in the orientation and flexibility of motifs in immediate proximity and across the artificial CH1–VL cross Fab interface and upstream elbow segment. Utilizing a hybrid database search, RNAseq, and a CRISPR/Cas9 knockout methodology in Chinese hamster ovary (CHO) production cell lines, procollagen-lysine, 2-oxoglutarate 5-dioxygenases (PLODs) were conclusively identified as the catalyzing enzymes accountable for the 5R-Hyl modification in TCB mAbs. To quantitatively inhibit Hyl formation in TCB mAbs, the activity of all three Chinese hamster PLOD isoenzymes needs to be depleted via CRISPR/Cas9 gene knockout. Moreover, our investigation identified cell culture iron availability, process duration, and clonal variability in CHO cells as elements influencing the levels of Hyl formation in TCB mAbs. This research offers a solution for circumventing Hyl formation in therapeutic complex mAb formats, such as TCB mAbs, produced in CHO cell culture processes, thereby addressing potential technical and biological challenges associated with unintended Hyl modification.